Irizin as a marker of diabetic myopathy in children with diabetes - Pashkova, O.; Chudova, N.; Stoiak, H.; Пашкова, Олена Єгорівна; Чудова, Наталя Ігорівна; Стояк, Г. В.; Пашкова, Е. Е.; Чудова, Н. И.; Стояк, А. В. (My University, 2020)
The purpose of the study: to study the amount of irizin in the blood serum of children with Type 1 diabetes considering the duration of clinical course and determine the role of irizin in diagnosing the diabetic myopathy. The study included 90 children with Type 1 diabetes (T1D) (average age 13,7±0,4 years old). Depending on the duration of the disease, 3 groups were formed: 1 group — 26 children under 1 year with T1D; group 2 — 27 children — duration of T1D from 1–5 years; group 3 — 37 children with T1D duration more than 5 years. The control group included of 25 conditionally healthy children of a representative age and gender. All children were evaluated for their muscle and fat mass and their indices, ultrasound examination of skeletal muscles, and determination of irisin levels in the blood serum by ELISA. It was established that with increasing durations of T1D there was a redistribution of the component body composition in the form of a decrease in the specific the muscle mass and an increase in the percentage of fat mass, as well as changes in the ultrasound pattern of skeletal muscles characterized by a decrease in the thickness of the muscle fibers, a infraction of the normal architecture of muscle and increased echogenicity of muscle bundles. It was established that in the first years of the disease, the decrease in muscle mass was accompanied by a decrease in the level of irisin, whereas with the prolonged course of T1D there was an increase in it, which was accompanied by loss of muscle mass and infraction of the architecture of skeletal muscles. Thus, increasing the level of irisin can be used as an additional marker for the development of diabetic myopathy. Мета дослідження: визначити рівень іризину у сироватці крові дітей, хворих на цукровий діабет 1 типу, в залежності від тривалості захворювання та його роль в діагностиці діабетичної міопатії. Було обстежено 90 дітей, хворих на цукровий діабет 1 типу (ЦД1) (середній вік 13,7 ± 0,3 років). В залежності від тривалості перебігу захворювання було сформовано 3 групи: 1 група — 26 дітей до 1 року захворювання на ЦД1; 2 група — 27 дітей — тривалість ЦД1 від 1–5 років; 3 група — 37 дітей з тривалістю ЦД1 більше 5 років. Групу контролю склали 25 умовно здорових дітей репрезентативних за віком та статтю. Всім дітям проводилась оцінка м’язової та жирової маси та їх індексів, ультразвукове обстеження скелетних м’язів та визначення рівня іризину у сироватці крові методом ІФА. Встановлено, що зі збільшенням тривалості ЦД1 відбувався перерозподіл компонентного складу тіла у вигляді зменшення питомої ваги м’язової та збільшення відсотку жирової маси, а також зміни ультразвукової картини скелетних м’язів, які характеризувались зменшенням товщини м’язового волокна, порушенням нормальної архітектоніки м’язу та підвищенням ехогенності м’язових пучків. Встановлено, що в перші роки захворювання зниження м’язової маси супроводжувалося зменшенням рівня іризину, натомість при тривалому перебігу ЦД1 відбувалося його підвищення, що супроводжувалося втратою м’язової маси та порушенням архітектоніки скелетної мускулатури. Таким чином, підвищення рівня іризину може використовуватись в якості додаткового маркеру розвитку діабетичної міопатії. Цель исследования: определить уровень иризина в сыворотке крови детей, больных сахарным диабетом 1 типа, в зависимости от длительности заболевания и его роль в диагностике диабетической миопатии. Было обследовано 90 детей, больных сахарным диабетом 1 типа (CД1) (средний возраст 13,7 ± 0,3 лет). В зависимости от длительности течения заболевания было сформировано 3 группы: 1 группа — 26 детей до 1 года заболевания СД1; 2 группа — 27 детей, продолжительность СД1 от 1–5 лет; 3 группа — 37 детей с продолжительностью СД1 более 5 лет. Группу контроля составили 25 условно здоровых детей репрезентативных по возрасту и полу. Всем детям проводилась оценка мышечной и жировой массы и их индексов, ультразвуковое исследование скелетных мышц и определения уровня иризина в сыворотке крови методом ИФА. Установлено, что с увеличением продолжительности СД1 происходило перераспределение компонентного состава тела с уменьшением удельного веса мышечной и увеличения процента жировой массы, а также изменения ультразвуковой картины скелетных мышц, которые характеризовались уменьшением толщины мышечного волокна, нарушением нормальной архитектоники мышци и повышением эхогенности мышечных пучков. Установлено, что в первые годы заболевания снижение мышечной массы сопровождалось уменьшением уровня иризина, в то время как при длительном течении СД1 происходило его повышение, которое сопровождалось потерей мышечной массы и нарушением архитектоники скелетной мускулатуры. Таким образом, повышение уровня иризина может использоваться в качестве дополнительного маркера развития диабетической миопатии.
Іризин як маркер діабетичної міопатї у дітей, хворих на цукровий діабет 1 типу
Иризин к ак маркер диабетической миопатии у детей, больных сахарным диабетом 1 типа
Keywords: myopathy; irisin; Type 1 diabetes; children; міопатія; іризин; цукровий діабет 1 типу; діти; миопатия; иризин; ахарный диабет 1 типа; дети